PERAN LEMBAGA SOSIAL SEBAGAI AGEN SOSIALISASI PENDIDIKAN DALAM PEMBENTUKAN KARAKTER - Himmatul Fauziyah; Tutuk Ningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the role of social institutions as agents of educational socialization in shaping the character, values, and behavior of learners. Education not only takes place formally in schools, but also through social institutions such as families, communities, religious organizations, and mass media that have a significant influence on individual development. The research method used is the study of literature by analyzing a variety of relevant literature on the function of social institutions in the educational process. The results showed that social institutions act as a liaison between individuals and their social environment through the process of internalization of values, norms, and culture. In addition, social institutions help expand the learning experience of students, strengthen formal education, and instill social skills needed in community life. Thus, social institutions are not only supporters of formal education, but also serve as strategic partners in shaping human character, knowledge, and noble character.